Impacts of the Early COVID-19 Pandemic on the Work of Bioethicists in Canada - Charron, Marilou; Bélisle-Pipon, Jean-Christophe; Couture, Vincent; Williams-Jones, Bryn; Ravitsky, Vardit; Dupras, Charles (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Bioethics experts played a key role in ensuring a coherent ethical response to the COVID-19 pandemic in the fields of healthcare, public health, and scientific research in Canada. In the province of Quebec, a group of academic and practicing bioethicists met periodically in the early months of the pandemic to discuss approaches and solutions to ethical dilemmas encountered during the crisis. These meetings created the opportunity for a national survey of bioethics practitioners from different fields. The survey, in which forty-five Canadian bioethics practitioners (clinical ethicists, ethicist members of REBs and government health policy ethicists, or any bioethicist practicing outside of academia) participated, explored their concerns, challenges and opportunities during the first wave of the pandemic, with the objective of informing bioethics research about the difficulties experienced by bioethicists “in the field”. Participants reported increased stress levels, increased workloads, and a greater proportion of their work being devoted to public health ethics. Most of their concerns focused on groups other than themselves, such as health professionals, patients, research participants, and people in vulnerable socio-economic situations. An optimism about the future of bioethics was noted due to an increased awareness of the importance of bioethics by the public and by health and research institutions.